Big on BK : current insights into the function of large conductance voltage- and Ca2+- activated K+ channels at the molecular, cellular and systemic levels /: current insights into the function of large conductance voltage- and Ca2+- activated K+ channels at the molecular, cellular and systemic levels. (2016) - Unknown
No abstract available